A new species of Acanthodactylus Fitzinger 1834 (Sauria: Lacertidae) from southern Iran - Heidari, Nastaran; Pouyani, Nasrullah Rastegar; Rastegar-Pouyani, Eskandar; Rajabizadeh, Mehdi (Zootaxa, 2013)
A new and distinctive species of lacertid genus Acanthodactylus Fitzinger, 1834 is described from 7 km east of Khamir Port, Hormozgan Province, southern Iran at an elevation of 30–40m above sea level (asl). Analyses of morphological characters and the comparison with other formerly known species of this genus have proven the status of this taxon as a new, distinct species. Combinations of scalation characters and distinct morphology, coloration and habitat peculiarities in calcareous mountains distinguish Acanthodactylus khamirensis sp.nov from all remaining species of the genus in the area. In order to show the validity of the new species, we carried out a comparative statistical analysis using 13 metric and six meristic morphological characters on all of the neighboring congeners of the new species using descriptive (one-way ANOVA) as well as multivariate analyses (PCA and DFA). The results confirm the specific status of the new taxon. Detailed information and an updated identification key for the genus Acanthodactylus in Iran are presented.